STRATEGI TRUE OR FALSE DENGAN MEDIA KARTU INDEKS PADA MATA KULIAH TEORI GRAF - Lukmanul Akhsani; Malim Muhammad (AlphaMath : Journal of Mathematics Education, 2016)
This study aims to determine the activities of students in learning subjects through True or False strategy of graph theory by media index cards. Observations show a more focused student activity because students already know the material of what will be learned through the index cards that they get in early learning, and they also know the form of matter or issue that they get when studying the learning material on which they will carry. Students focus on the material presented by the lecturers. At the end of the students' learning spirit in concluding that material has been obtained. Lecturers also seem satisfied when getting feedback from students on material that has been given to the student lecturer. Keyword: true or false, cards, graphs, media